2018
DOI: 10.1155/2018/6274072
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Adsorption of Proinflammatory Cytokines by Graphene Nanoplatelets and Their Composites for Extracorporeal Detoxification

Abstract: Sepsis is a complex clinical syndrome that features excessive release of cytokines and other inflammatory mediators that could lead to organ dysfunction. Despite different treatment and management options, sepsis associated high morbidity and mortality rates remain. This has prompted intensive research into alternative therapeutic approaches such as targeted removal of sepsis related molecules using extracorporeal hemoperfusion. In this study, we explore the use of graphene nanoplatelets (GNP) as lowcost alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…than 100 times the original [29]. TEM images showed that GnP agglomerate consisted of submicron size particles [30] indicating that each GnP particle is formed by stacks of graphene layers. To understand the difference in the adsorption capacity of carbon materials with different surface functional groups, a detailed XPS analysis of their surface chemistry was performed ( Table 1).…”
Section: Porosity and Surface Chemistry Of Carbon-based Materialsmentioning
confidence: 97%
See 2 more Smart Citations
“…than 100 times the original [29]. TEM images showed that GnP agglomerate consisted of submicron size particles [30] indicating that each GnP particle is formed by stacks of graphene layers. To understand the difference in the adsorption capacity of carbon materials with different surface functional groups, a detailed XPS analysis of their surface chemistry was performed ( Table 1).…”
Section: Porosity and Surface Chemistry Of Carbon-based Materialsmentioning
confidence: 97%
“…BSA solutions were prepared in phosphate-buffered saline, PBS (pH 7.2). Kinetic studies were conducted with BSA solutions (1 mg/mL) at varying adsorption times (5,10,20,30, 60 and 90 min) at room temperature while shaking at 150 rpm. Prior to BSA adsorption, expanded graphite (~100 mg) was equilibrated overnight in PBS (2.0 mL) to prevent adsorption of environmental contaminants from the air and then the excessive liquid phase was separated by centrifugation.…”
Section: Adsorption Of Bovine Serum Albumin (Bsa)mentioning
confidence: 99%
See 1 more Smart Citation
“…153,154 GDs had been shown to stimulate immune cells to produce different responses. 155,156 In this subsection, we reviewed the immunomodulatory mechanism of GDs-induced bone regeneration, which was normally in two ways.…”
Section: Immunomodulatory Mechanism Of Gds-induced Bone Regenerationmentioning
confidence: 99%
“…Treatment with CDCs postannealed in Ar or NH 3 and synthesized from <38 µm sized precursor particles facilitated the highest removal efficiency of all cytokines (99-100%) within 60 min. This study highlights the importance of NPs synthetic identify for efficient blood purification and fueled the design of other carbon-based NPs, [119,120] such as graphene nanoplatelets, [121,122] with cytokines adsorption capacity.…”
Section: Np-enabled Alternative Methods To Combat Sepsismentioning
confidence: 89%